[PP.07.12] ARMC5 MUTATIONS IN PATIENTS WITH PRIMARY ALDOSTERONISM AND BILATERAL ADRENAL LESIONS. (September 2016) - Mulatero, P.; Schiavi, F.; Williams, T.A.; Monticone, S.; Barbon, G.; Opocher, G.; Fallo, F.
Abstract : Objective: Primary aldosteronism (PA) is the most frequent form of secondary hypertension and bilateral adrenal hyperplasia (BAH) is the most common PA subtype. The molecular mechanisms responsible for the development of BAH are still unknown, but the bilateral involvement of the adrenal glands suggests a potential predisposing genetic defect. Heterozygous germline mutations of armadillo repeat containing 5 (ARMC5) cause hypercortisolism due to sporadic primary bilateral macronodular adrenal hyperplasia and have been also observed in African-American patients affected by PA. We investigated the presence of germline ARMC5 mutations in a cohort of PA patients who had bilateral adrenal alterations detectable at CT-scanning. Design and method: We retrospectively assessed 39 consecutive patients with PA (25 males and 14 females) at the Division of Internal Medicine and Hypertension Unit of the University of Torino between 2010 and 2014. All patients had bilateral alterations of the adrenals at CT-scanning. Results: Thirty-nine PA patients (37 Caucasians and 2 black Africans; 8 unilateral, 27 bilateral and 4 undetermined subtype) with bilateral adrenal lesions were included in the study. The entire coding region of ARMC5 and all intron/exon boundaries were succesfully sequenced in all 39 patients; we identified 11 common variants, 5 rare variants with a minor allele frequency <1% and 2 new variants not previously reported in public databases. We did not detect by in silico analysis any ARMC5 sequence variations that were predicted to alter protein function. Conclusions: To conclude, ARMC5 mutations are not present in a fairly large series of Caucasian patients with PA and bilateral adrenal lesions. Further studies are warranted to definitively clarify the involvement of ARMC5 in the pathogenesis of adrenal nodules and aldosterone excess in PA patients.